Performance Evaluation and Management of Indian Manufacturing Organizations Through Fuzzy Optimization Techniques - Agrawal, Ankur; Agarwal, Reema; Agrawal, Bhavna; Pandey, Sudha; Kumari, Archana (International Journal of Experimental Research and Review, 2024)
In a context of intense competition, evaluating financial performance is crucial for manufacturing sectors. As such, a precise and fitting performance review is essential. In the process of evaluation, financial performance indicators need to be carefully chosen because they show how competitive a business is. In this paper, the financial performances of the firms in the Indian manufacturing industry are evaluated using financial ratios, specifically accounting-based financial performance (AFP) measures and value-based financial performance (VFP) measures. These financial performances are assessed through multi-criteria decision-making (MCDM) techniques, specifically fuzzy multi-objective and optimization on the basis of ratio analysis (F-MOORA) and fuzzy step-wise weight assessment ratio (F-SWARA). First, the financial performance indicators' weights are determined by the F-SWARA approach, and then the firms' rankings are determined by the F-MOORA approach. By applying SWARA methodology in a fuzzy environment, the implications of the findings demonstrate that the factor named Return on Assets (ROA) contains the maximum weight and the factor named regret contains the lowest weight. By applying F-MOORA technique, it also demonstrates that company C1 is the best and company C3 is the worst.